Analisis Ta'kid Al-Madh Bima Yusybih Al-Dzamm Danta'kid Al-Dzamm Bima Yusybih Al-Madh dalam Surah Al Qolam Ayat 4 dan Surat Al Ma’un Ayat 4-5 - Annisa Khairida Pasaribu; Berliana Sari Harahap; Harun Al-Rasyid (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study explores the concepts of ta'kid al-madh bima yusyibih al-dzamm and ta'kid al-dzamm bima yusyibih al-madh in the Qur'an. Ta'kid al-madh bima yusyibih al-dzamm refers to reinforcing praise by using expressions that resemble criticism, while ta'kid al-dzamm bima yusyibih al-madh involves strengthening censure through expressions that appear to praise. This research employs a library research method focusing on textual analysis of the Qur'an. It relies on primary sources, including classical tafsir texts, books on balaghah (Arabic rhetoric), and relevant Arabic linguistic literature. The analysis examines two verses: In Surah Al-Qalam (68:4), praise for the Prophet Muhammad (PBUH) is emphasized through rhetorical expressions such as inna, 'ala, and khuluqin 'azhim, highlighting his exalted moral character that surpasses all human standards. Conversely, in Surah Al-Ma'un (107:4-5), censure is directed at those who pray but are negligent. The technique of ta'kid al-dzamm is applied by using the act of prayer—usually praiseworthy—to underscore the severity of their negligence in worship.